ANALISIS PEMBELAJARAN DARING PADA MATERI SIFAT DAN PERUBAHAN WUJUD BENDA DI KELAS V SDN KEDALEMAN IV CILEGON - Issolihah, Khairin Nisa; Wuryastuti, Sri; Suratno, Tatang (Didaktika, 2021)
The covid-19 pandemic is turning the originally face-to-face education system into online learning. Online learning is one form of educational innovation that answers the challenges of the availability of varied learning resources and adaptation of learning activities to achieve academic goals. Therefore, during the pandemic, online learning is necessary for learning to continue at the elementary school level. The purpose of this study is to know the planning, implementation, and evaluation of online learning activities on materials of the nature and changes of the shape of objects in 5th grade of SDN Kedaleman IV Cilegon in the 2020/2021 school year. This study uses a qualitative approach and case study method. The subjects of this study were four students and four parents in 5th grade of SDN Kedaleman IV Cilegon participated in online learning activities. Data collection techniques include in-depth interviews, non-participant observations, and documentation. This study's data analysis techniques include data collection, data reduction, data presentation, and conclusion drawing. The results showed that online learning in 5th grade of SDN Kedaleman IV Cilegon has the following stages: Planning stages such as determining the application used, creating WhatsApp groups, preparing learning materials, tools, and supporting materials in online learning, choosing learning methods and media. The implementation stage involves preliminary, core, and closing activities by using facilities in supporting online learning activities, namely virtual face-to-face and LMS. The evaluation phase consists of an evaluation of tests (assessment of knowledge with an assignment of questions and assessment of skills with practical tasks) and evaluation of online learning implementation programs (advantages and disadvantages and constraints and solutions)